Triptyque Silviu Purcărete : le théâtre comme infidélité - Nechit, Diana; Șerban, Andrei (Symbolon, 2021)
Triptych Silviu Purcărete: Theatre as Infidelity Silviu Purcărete is one of the most appreciated creators in recent theatre history, a fact which has given him international fame, thanks to the special way in which he tackles the canonical texts of universal literature. This paper, far from being considered exhaustive, doesn’t necessarily aim to introduce rigid criteria of the universe of Purcărete, but to propose a critical analysis entwined with an exercise in admiration. We will try to surprise some of his structural obsessions, by relying on three of the most popular performances signed by the director on the stage of the “Radu Stanca” National Theatre in Sibiu: “Faust”, “Metamorphoses”, “The Scarlet Princess”.